2013
DOI: 10.3139/146.110861
|View full text |Cite
|
Sign up to set email alerts
|

Hot forming of a new steel used in stamping dies and tooling

Abstract: The hot forming behavior of a new steel used in manufacturing processes at high temperatures such as hot stamping has been studied in this article. Compression and tensile tests were performed at low and high strain rates in a temperature range of 1 173–1 473 K to simulate forming processing conditions. The deformation data obtained from these experiments were correlated with the Garofalo equation with a stress exponent of 4.4 and an activation energy of 277 kJ · mol−1. This equation was used to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It is found that the cold punch combined with the hot die can reduce the springback up to 20% when compared to conventional room temperature bending test in the sheet forming process of U-bend aluminum 1050. The experimental investigations in hot forming process can be found in the latest publications [ 7 – 9 ]. Temperature in the springback prediction is becoming a topic that could be improved in the future investigation [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the cold punch combined with the hot die can reduce the springback up to 20% when compared to conventional room temperature bending test in the sheet forming process of U-bend aluminum 1050. The experimental investigations in hot forming process can be found in the latest publications [ 7 – 9 ]. Temperature in the springback prediction is becoming a topic that could be improved in the future investigation [ 2 ].…”
Section: Introductionmentioning
confidence: 99%